Penerapan latihan shutle run dalam meningkatkan kelincahan footwork atlit bulutangkis - Musawwir, Musawwir; Nur, Suaib; Riswanto, A. Heri (Universitas Hamzanwadi, 2023)
This study aims to analyze the effectiveness of shuttle run training in improving footwork agility of badminton athletes PB Mandiri Husada Palopo. Reliability of footwork is very important in this game, but often athletes experience problems coordinating foot movements that affect performance. Shuttle run training was chosen because it mimics the movements in badminton games with fast and repetitive movements. This research method uses a pre-experimental one-group pretest-posttest design. The sample consisted of 15 athletes PB Mandiri Husada Palopo aged 13-16 years. Data was collected through initial and final tests to compare changes in footwork agility after training. Results showed significant improvements in agility categories, with more athletes achieving